Classroom Management Model in Making Islamic Religious Education Effective - Agil; Ahmad Faris Noval Yahya; Aftrian Amelia; Bintan Mumtazah; Habibullah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study discusses the importance of classroom management in Islamic Religious Education (PAI) learning, given that effective classroom management plays a strategic role in creating a conducive, orderly, and religious learning environment. Such an environment is needed to support the achievement of PAI learning objectives, namely the formation of students’ noble character and morality. This study aims to analyze the concepts, strategies, and implications of classroom management in PAI learning through a literature study approach. The method used is a literature study by collecting and analyzing various primary and secondary sources relevant to the research topic. Primary sources include the Qur’an, hadith, and books of Qur’anic exegesis, while secondary sources consist of books, scientific journals, undergraduate research papers (skripsi), and articles related to classroom management and PAI learning. Data analysis techniques were carried out through reduction, categorization, and synthesis. The results show that classroom management in PAI learning can be implemented through strategies of arranging the physical classroom environment, managing humanistic and religious learning interactions, and applying discipline based on Islamic values. Teachers act as facilitators, motivators, and role models. Supporting factors include teacher competence and facilities, while hindering factors encompass students’ readiness and limitations in learning facilities.